The utility of Magic Lens interfaces on handheld devices for touristic map navigation - Grubert, Jens; Pahud, Michel; Grasset, Raphael; Schmalstieg, Dieter; Seichter, Hartmut (Pervasive and Mobile Computing, 2015)
This paper investigates the utility of the Magic Lens metaphor on small screen handheld devices for map navigation given state of the art computer vision tracking. We investigate both performance and user experience aspects. In contrast to previous studies a semi-controlled field experiment (n = 18) in a ski resort indicated significantly longer task completion times for a Magic Lens compared to a Static Peephole interface in an information browsing task. A follow-up controlled laboratory study (n = 21) investigated the impact of the workspace size on the performance and usability of both interfaces. We show that for small workspaces Static Peephole outperforms Magic Lens. As workspace size increases performance gets equivalent and subjective measurements indicate less demand and better usability for Magic Lens. Finally, we discuss the relevance of our findings for the application of Magic Lens interfaces for map interaction in touristic contexts.